Post a New Question


posted by .

how would you simplify this equation:

y = (x+3)/[(4-sqrt(16+h))]

please help me!

you have three variables. I am not certain "simplify" is an appropriate term here.

ohhhh it was my mistake. I meant:

y = h/[(4-sqrt(16+h))]

y = h/[(4-sqrt(16+h))]
rationalize the denominator..

y = h/[(4-sqrt(16+h))] *(4+sqrt(16+h)/(4+sqrt(16+h)

you finish it. check my work.

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question